IMPROVING AML/CFT RISK-BASED APPROACH IN SERBIAN BANKS: EVIDENCE FROM A SURVEY - La Torre, Maura; Nikolic, Marija (European Scientific Journal, ESJ, 2014)
The aim of this paper is to give a contribute in searching solutions to improve the antimoney laundering (AML)/Combating financing of terrorism (CFT) risk-based approach in banks. To achieve this goal, we decided to directly involve the banks, calling them for a kind of self-assessment about some factors associated with the performace of their AML/CFT riskbased approach. For this purpose, we carried out a survey, in the period between September 2013 and October 2013, addressed to a sample of banks in the Republic of Serbia. The answers provided have identified some factors that banks consider strategic to improve the internal AML/CFT risk-based approach and, at the same time, highlighted some deficiencies charged to regulators and supervisors.